Body size from birth to middle age and the risk of hip and knee replacement. - Liu, B; Balkwill, A; Green, J; Beral, V (BioMed Central, 2016)
Background Information regarding the effects of body size in childhood and early adulthood on the risk of hip and knee replacement in later life is inconsistent. We aimed to assess their effect, taking into account body mass index (BMI) in middle-age. Methods Prospective cohort (Million Women Study) of 791,034 women with information on birth weight, body size at age 10 and age 20, and current BMI (at mean age 59.5 years) were followed for 6.82 million person-years. Adjusted relative risks (RRs) and absolute risks of hospitalisations for hip or knee replacement surgery for osteoarthritis were estimated. Results After a mean of 8.6 years follow-up, 17,402 women had a hip replacement and 18,297 a knee replacement. Between the ages of 50 and 79 years, absolute risks for women with current BMIs of <22.5 kg/m2 and 35+kg/m2 were respectively 5.6 and 13.2 % for hip replacement; and 2.6 and 35.1 % for knee replacement. Within each category of current BMI, increasing body size at age 10 and at age 20 had comparatively small effects; there were no significant associations with birth weight. We estimate that 40 % of UK women with a BMI 35 + kg/m(2) have either a hip or knee replacement between the ages of 50-79 years; this compares to just 10 % of UK women with a healthy BMI (<25 kg/m2). Conclusions The effects of body size in childhood and early adulthood on the absolute risks of either a hip or knee replacement are minimal compared to the effect of adiposity in middle age.